2020
DOI: 10.1542/peds.2020-0444
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Individuals With Metabolic Diseases Identified Through Newborn Screening

Abstract: BACKGROUND: Although extended newborn screening (NBS) programs have been introduced more than 20 years ago, their impact on the long-term clinical outcome of individuals with inherited metabolic diseases (IMDs) is still rarely investigated. METHODS: We studied the clinical outcomes of individuals with IMDs identified by NBS between 1999 and 2016 in a prospective multicenter observational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 28 publications
2
89
0
1
Order By: Relevance
“…This emphasizes the need to optimize the diagnostic NBS process to that NBS results are available early, preferably before or by day 5, to prevent life-threatening and prognostically relevant severe neonatal decompensations. 3,16 Despite positive NBS result, the subsequently implemented therapeutic strategies for classical IVA neither were sufficient to prevent metabolic decompensations in 25% patients after the diagnosis was known nor the manifestation of recurrent episodes in 41% of decompensated individuals with classic IVA. Here, evaluation of impact of therapy on outcome in classic IVA in larger international cohorts and deducted guidelines for therapy of classic IVA are urgently needed, especially for the vulnerable period in infancy and childhood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This emphasizes the need to optimize the diagnostic NBS process to that NBS results are available early, preferably before or by day 5, to prevent life-threatening and prognostically relevant severe neonatal decompensations. 3,16 Despite positive NBS result, the subsequently implemented therapeutic strategies for classical IVA neither were sufficient to prevent metabolic decompensations in 25% patients after the diagnosis was known nor the manifestation of recurrent episodes in 41% of decompensated individuals with classic IVA. Here, evaluation of impact of therapy on outcome in classic IVA in larger international cohorts and deducted guidelines for therapy of classic IVA are urgently needed, especially for the vulnerable period in infancy and childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The national multicenter observational study included individuals with IVA identified by NBS between 1 January 1998 and 31 December 2018, significantly extending the prospective multicenter observational NBS study in Southwest Germany (DRKS-ID: DRKS00013329 16 ). Inclusion criteria were (a) positive NBS result, (b) confirmation of IVA according to the national NBS guideline, 22 and (c) written informed consent of patients and/or caregivers.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…If diagnosed and treated early, prognosis is generally good 12,13 . MSUD is managed by a protein‐restricted diet with BCAA‐free formula supplementation 2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…When oral or enteral administration is difficult or impossible (ie, in cases of vomiting, coma or seizures), or in case of refusal of nasogastric tube feeding, an intravenous (IV) formula may be necessary 15‐17 . Although not widely available in Europe, IV BCAA‐free formula has been used in France since 2010 for the treatment of metabolic decompensation episodes in emergency settings or in combination with or as an alternative to invasive extracorporeal procedures, such as hemodialysis and/or hemofiltration (HD/HF) 12‐14 …”
Section: Introductionmentioning
confidence: 99%